## AbdulRehman 4 years ago Why (-)*(-)=(+).

1. amistre64

hmmm....... multiplication is adding really if you add the opposite of 3 that opposite of 5 times we get what?

2. amistre64

the opposite of 3; 5 times = -3 -3 -3 -3 -3 = -15 so the opposite of 5 times gets you to 15

3. amistre64

-(-3)-(-3)-(-3)-(-3)-(-3) = 15

4. amistre64

does that make sense?

5. AbdulRehman

it takes me to other sense that is (-1)*x=1 then x=(-1)

6. nowhereman

Do you understand / accept (-1)*(1) = -1 ?

7. AbdulRehman

yeah

8. nowhereman

So then you get $0 = 0\cdot 0 = (a-a)\cdot(b-b) = (a+(-a))\cdot(b+(-b))$so using distributivity$= a\cdot b + a\cdot (-b) + (-a)\cdot b + (-a)\cdot(-b) = a\cdot b - a\cdot b - a\cdot b + (-a)\cdot (-b)$thus altogether $0= (-a)\cdot(-b) - a\cdot b$ and that means nothing else than $(-a)\cdot(-b) = a\cdot b$

9. amistre64

phhhhbbbtttt!!! how needs proofs ;)

10. nowhereman

hehe, Mathematics needs it, or from a certain point on anything will be arbitrary because you can't tell intuitively what's true and what's false.

11. nowhereman

btw 555 medals, awesome work there :-)